Single-cell RNA sequencing and ATAC sequencing identify novel biomarkers for bicuspid aortic valve-associated thoracic aortic aneurysm - Liu, Xu-Wen; Wang, Pei; Zhang, Li; Zhu, Yu; Zhai, Jun-Yu; Wang, Chang-Nan; Li, Jun; Xiao, Jian (Frontiers in Cardiovascular Medicine, 2024)
Bicuspid aortic valve (BAV) is the most prevalent congenital cardiovascular defect and known to cause thoracic aortic aneurysms (TAAs). To improve our understanding of BAV pathogenesis, we characterized the cellular composition of BAV tissues and identified molecular changes in each cell population. Tissue samples from two patients with BAV and two heart transplant donors were analyzed using single-cell RNA sequencing, assay for transposase-accessible chromatin using sequencing, and weighted gene coexpression network analysis for differential gene analysis. TAArelated changes were evaluatedby comparing the proportion of each cell type and gene expression profiles between TAA and control tissues. Further, by combining our singlecell RNA sequencing data with publicly available data from genome-wide association studies, we determined critical genes for BAV. We found 20 cell subpopulations in 2 TAA tissues, including multiple subtypes of smooth muscle cells, fibroblasts, macrophages, and T lymphocytes. This result suggested that these cells play multiple functional roles in BAV development. Several differentially expressed genes, including CD9, FHL1y, HSP90AA1, GAS6, PALLD, and ACTA2, were identified. We believe that this comprehensive assessment of the cellular composition of TAA tissues and the insights into altered gene expression patterns can facilitate identification of novel diagnostic biomarkers and therapeutic targets for BAV-associated TAA.